A Systematic Literature Review of MSME’s Internal Control - Chandra Pramana, Andy (Universitas Kadiri, 2024)
This article is a Systematic Literature Review that aims to summarize the results of previous research on MSME's internal control. The Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) technique is used with the help of a tool called Watase UAKE. The filtration used is articles spread across Scopus Q1, Q2, Q3 and Q4 with a time span of 2015 to 2025. The review results show that 2022 is the year in which this topic is most researched, producing 2 articles. The countries of origin of researchers are spread across Brazil, Egypt, Indonesia, Sweden, USA and Spain. The most cited article is an article by Johnstone & Leanne in 2022 entitled the means to substantive performance improvements - environmental management control systems in ISO 14001- certified SMEs. This article result is about SMEs often having difficulty in designing and monitoring environmental control because it involves external aspects such as audits and regulations. As a result, the Environmental Management and Control System or EMCS they developed is broad and complex, spanning strategic and operational levels, and involving parties outside the organization. This article has been cited 10 times.